Pharmacological inhibition of protease‐activated receptor‐2 reduces crescent formation in rat nephrotoxic serum nephritis. (25th March 2019) - Han, Yingjie; Tian, Lifang; Ma, Frank; Tesch, Greg; Vesey, David A.; Gobe, Glenda C.; Lohman, Rink‐Jan; Morais, Christudas; Suen, Jacky Y.; Fairlie, David P.; Nikolic‐Paterson, David J.
Summary: Glomerular crescent formation is a hallmark of rapidly progressive forms of glomerulonephritis. Thrombosis and macrophage infiltration are features of crescent formation in human and experimental kidney disease. Protease‐activated receptor‐2 (PAR‐2) is a G‐protein coupled receptor that links coagulation and inflammation. This study investigated whether pharmacological inhibition of PAR‐2 can suppress glomerular crescent formation in rat nephrotoxic serum nephritis (NTN). Disease was induced in Wistar Kyoto rats by immunisation with sheep IgG followed by administration of sheep nephrotoxic serum. Rats (n = 8/group) received the PAR‐2 antagonist (GB88, 10 mg/kg/p.o.), vehicle or no treatment starting 3 days before nephrotoxic serum injection and continuing until day 14. Vehicle and untreated rats developed thrombosis and macrophage infiltration in the glomerular tuft and Bowman's space in conjunction with prominent crescent formation. Activation of JNK signalling and proliferation in parietal epithelial cells was associated with crescent formation. GB88 treatment significantly reduced crescent formation with a substantial reduction in glomerular thrombosis, reduced macrophage infiltration in Bowman's space, and reduced activation of parietal epithelial cells. However, GB88 did not protect against the development of proteinuria, renal function impairment, inflammation or tubular cell damage in the NTN model. In conclusion, PAR‐2 plays a specific role in glomerular crescent formation by promoting glomerular thrombosis, macrophage accumulation in Bowman's space and activation of parietal epithelial cells.